تعليم اللغة العربية القائم على التعلم التفاضلي في مدرسة محمدية الثانوية السابعة فانجنغ - Wati, Andini Fahmiyah; Hasanah, Mamluatul (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2024)
ABSTRACT Differentiated learning is learning that accommodates students' learning needs. The teacher facilitates students according to their needs, because each student has different characteristics, so they cannot be given the same treatment. This differentiation learning will guide students by themselves to be motivated and enthusiastic in learning because they learn according to their preferred learning style or profile. The purpose of this study was to find out (1) differentiation-based Arabic learning at Muhammadiyah Seven Panceng High Schools (2) the characteristics of learning Arabic based on differentiation at Muhammadiyah Seven Panceng High Schools. This research uses descriptive qualitative method. The results of the study showed that the characteristics of differentiation-based Arabic learning at Muhammadiyah Seven Panceng High School were Initial Assessment, Flexibility in Material Choices, Various Learning Strategies, Heterogeneous Group Work, Individual Guidance, Choice of Tasks and Assessment. In practice, the teacher divides the student groups into three groups, namely the visual group, the audio group, and the kinesthetic group. Then each group is given recitation material in a different way or delivery of material, for the visual group the material is presented in the form of pictorial and colorful writing, the audio group is shown a video, and the kinesthetic group is presented with writing pasted on the board. After that they discussed the material with their respective groups. Then they take turns presenting the results of the discussion in front of the teacher and other groups. Prior to the implementation of the differentiation-based Arabic language learning model, a learning style test was held in order to determine the learning style of each student in order to achieve learning goals. Each learning style has differences both in terms of content, process, product and learning environment. The Arabic language learning based on differentiation in each school is different and Muhammadiyah Seven Panceng High Schools has its own characteristics ملخص تعليم التفاضلي هو التعليم الذي يلائم احتياجات التعلم للطلاب. يقوم المعلم بتسهيل الطلاب وفقًا لاحتياجاتهم ، لأن لكل طالب خصائص مختلفة ، فلا يمكن أن يحصلوا على نفس المعاملة. سيرشد تعليم التفاضلي الطلاب بأنفسهم ليكونوا متحمسين ومتحمسين للتعلم لأنهم يتعلمون وفقًا لأسلوب التعلم المفضل لديهم أو ملفهم الشخصي. كان الغرض من هذه البحث هو اكتشاف (١) تعليم اللغة العربية القائم على التعلم التفاضلي في مدرسة محمدية الثانوية السابعة فانجنغ (٢) خصائص تعليم اللغة العربية على أساس التفاضلي في مدرسة محمدية الثانوية السابعة فانجنغ . يستخدم هذا البحث المنهج الوصفي النوعي. أما نتيجة هذا البحث هو أن خصائص تعليم اللغة العربية القائم على التعام التفاضلي في مدرسة محمدية الثانوية السابعة فانجنغ كانت التقييم الأولى ، والمرونة في الخيارات المادية ، واستراتيجيات التعلم المختلفة ، والعمل الجماعي غير المتجانس ، والتوجيه الفردي ، واختيار المهام والتقييم. في الممارسة العملية ، يقسم المعلم مجموعات الطلاب إلى ثلاث مجموعات ، وهي المجموعة المرئية والمجموعة الصوتية والمجموعة الحركية في مدرسة مدرسة محمدية الثانوية السابعة فانجنغ . ثم تم إعطاء كل مجموعة مادة تلاوة بطريقة مختلفة أو تسليم مادة ، بالنسبة للمجموعة المرئية ، تم تقديم المادة على شكل كتابة مصورة وملونة ، وعرضت المجموعة الصوتية مقطع فيديو ، وتم تقديم المجموعة الحركية مع كتابة ملحقة إلى السبورة. بعد ذلك ناقشوا المواد مع مجموعاتهم. ثم يتناوبون على عرض نتائج المناقشة أمام المعلم والمجموعات الأخرى. قبل تنفيذ نموذج تعليم اللغة العربية القائم على التعلم التفاضلي ، تم إجراء اختبار أسلوب التعلم من أجل تحديد أسلوب التعلم لكل طالب من أجل تحقيق أهداف التعلم. لكل نمط تعلم اختلافات من حيث المحتوى والعملية والمنتج وبيئة التعلم. يختلف تعليم اللغة العربية على أساس التعلم التفاضلي في كل مدرسة ، ويتميز في مدرسة محمدية الثانوية السابعة فانجنغ بخصائصه الخاصة